Pengembangan Video Pembelajaran Bernuansa Nilai Karakter Nasionalisme pada Materi Pecahan Kelas V Sekolah Dasar Islam Al-Azhar - Sri Wahyuni; Bistari Bistari; Kartono Kartono; Hamdani Hamdani; Suparjan Suparjan (ISLAMIKA, 2023)
This have a look at ambitions to produce a product inside the shape of a mastering video with nuances of the price of the character of nationalism in fractional cloth for 5th grade students of Al-Azhar Islamic elementary faculty according to the evaluation of media professionals, fabric experts and college students. The research method used is research and development (RnD) by means of adopting the Borg and Gall version. The facts resources of this examine have been media expert validators, cloth professional validators, a trainer and twenty- 5th grade college students of Na'im Islamic basic faculty Al-Azhar. The studies gadgets used were interview tips, preresearch questionnaires, needs analysis sheets for instructors, desires evaluation sheets for college students, media professional validation questionnaires, cloth expert validation questionnaires, pupil use response questionnaires and documentation. The system of growing a getting to know video with nuances of nationalism person values in fractional fabric is going through 7 degrees, namely the preliminary take a look at stage and facts accumulating, planning, preliminary product improvement and validation, first level trial, revision, 2d stage trial, and revision. The effects of product validation via media specialists reached a mean of 4.2 (very valid) and the consequences of validation achieved by cloth professional validators changed into four.1 (very valid). further, product trials in st age I acquired a percentage of 84% with standards superb and within the 2d phase of the product trial, it received a percentage of 92% which had very good standards